Die Suid-Afrikaanse lugmag se optrede in die teaters van Noord-Namibië en Suid-Angola 1983-1985: 'n historiese verkenning - Barnard, Leo (Faculty of Humanities, University of the Free State, 2009)
In comparison with the preceding years the period from 1983 to 1985 was, as far as the action of the SAAF in the Border War was concerned, relatively quiet. The few big operations in the north of Namibia, as well as cross-border operations in the south of Angola, are analysed in detail. After Operation Askari a period of relative peace followed as the Monitering Commission was established. The action of the SAAF during Operations Boswilger, Egert and Welmesh brought an end to this. The hostilities built up to such an extent that the end of this period can be seen as the lull before the storm.
Keywords: South African Air Force; Border War; Cross-border operations; Namibian operations